Digital Marketing and Public Speaking Training for Generation Z - Agoestyawati, Redjeki; Estiana, Ria; Makmuroh, Umi Hanik; Akhmad, Jaenudin (Commercium : Journal of Business and Management, 2024)
Generation Z has extensive and natural access to the internet, mobile devices, social media, and other technological innovations from an early age. Friendly interactions with technology have shaped the way Generation Z communicates, learns, and connects. The importance of career readiness in facing the ever-growing digital era is very crucial. Rapid technological transformation has changed the work landscape significantly. Many new jobs are emerging, while others are experiencing fundamental changes in skill demands. The abilities that generation Z needs to have are the ability to communicate and collaborate as well as digital marketing skills. The method of implementing the activity uses various methods such as lectures, discussions, questions and answers, as well as providing digital marketing and public speaking training for students to prepare them for entering the world of work and entrepreneurship. The results of the activity are that the lecturers provide digital marketing and public speaking training for students to become entrepreneurs and the lecturers provide motivation so that students are able to face preparations for entering the world of work and can continue to university level.